Native or non-native english teacher at ECCI University in the modern languages program (2016)
The purpose of this study is to find out the perceptions some of the students of 7th and 8th semester in the ML (Modern Languages) program at ECCI university have, which will be based on three main constructs such as student’s satisfaction degree regarding their English learning, student’s perception about their learning progress with NETs (Native English Teacher) or Non NETs (Non Native English Teachers) and student’s expectations when enrolling on the ML program. In order to develop this study we will research information from different sources and authors, we will also apply different investigation tools like surveys and interviews. These tools will provide us with a clear idea of the students’ point of view about the topic previously mentioned.